2015
DOI: 10.1038/bcj.2015.75
|View full text |Cite
|
Sign up to set email alerts
|

Managing chronic myeloid leukaemia in the elderly with intermittent imatinib treatment

Abstract: The aim of this study was to investigate the effects of a non-standard, intermittent imatinib treatment in elderly patients with Philadelphia-positive chronic myeloid leukaemia and to answer the question on which dose should be used once a stable optimal response has been achieved. Seventy-six patients aged ⩾65 years in optimal and stable response with ⩾2 years of standard imatinib treatment were enrolled in a study testing a regimen of intermittent imatinib (INTERIM; 1-month on and 1-month off). With a minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…Nevertheless, numerous studies have demonstrated the persistence of cML leukemic cells in the BM niche following treatment, even in patients with undetectable levels of the BCR-ABL1 transcript by RT-qPcR. The persistence of these cells in patients with CML has also been confirmed in clinical practice, where molecular relapse is experienced in ~50% of patients undergoing TKI discontinuation programs (39)(40)(41)(42). Residual leukemic cells may be quiescent stem cells, detectable only by cd26 recognition methods (43), or active cML cells.…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, numerous studies have demonstrated the persistence of cML leukemic cells in the BM niche following treatment, even in patients with undetectable levels of the BCR-ABL1 transcript by RT-qPcR. The persistence of these cells in patients with CML has also been confirmed in clinical practice, where molecular relapse is experienced in ~50% of patients undergoing TKI discontinuation programs (39)(40)(41)(42). Residual leukemic cells may be quiescent stem cells, detectable only by cd26 recognition methods (43), or active cML cells.…”
Section: Introductionmentioning
confidence: 96%
“…[110]). has been achieved [111,112]. However, the length and frequency of intervals to allow catchup growth in children on TKI treatment still have to be defined and at least in our rat model, this approach did not recover the biomechanical strength of the long bones.…”
Section: Hypothesized Model Of Osseous Damage and Clinical Relevance mentioning
confidence: 81%
“…Our animal model also revealed that intermittent imatinib treatment mitigated skeletal effects on the growing bone, thus pointing toward a possibility to improve the risk-benefit ratio of long-term TKI exposure in pediatric patients. First clinical data in adults look promising but further studies must be carried out to determine whether the intermittent exposure is also sufficiently effective for the control of CML [111,112]. Regarding pediatric patients, the results from the juvenile animal model and the clinical experience from adult patients with CML should be combined.…”
Section: Experimental Animal Models Of Human Diseases -An Effective Tmentioning
confidence: 99%
“…1 ); 23 reporting non-standard dosing of oral SACT in solid tumours and 11 in haematological malignancies. Four studies were late phase clinical trials [ 20 23 ], 15 were cohort studies and 15 were case reports. Non-standard dosing was identified for eleven different oral SACT, as reported in Tables 3 - 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Non-standard dosing strategies reported were dose interruptions, dose reductions and a variety of other strategies. Dose interruption strategies were the most common non-standard dosing strategy described (14 studies), dose reductions (9 papers), and other dosing strategies (11 studies, of which, two reported the use of alternate day dosing of lenalidomide [ 11 , 23 ]).
Fig.
…”
Section: Resultsmentioning
confidence: 99%